Preparation and characterization of novel as-cast Ti-Mo-Nb alloys for biomedical applications - Cardoso, Giovana Collombaro [UNESP]; de Almeida, Gerson Santos [UNESP]; Corrêa, Dante Oliver Guim [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Buzalaf, Marília Afonso Rabelo; Correa, Diego Rafael Nespeque [UNESP]; Grandini, Carlos Roberto [UNESP] (Springer Nature, 2022)
Ti and its alloys are the most used metallic biomaterials devices due to their excellent combination of chemical and mechanical properties, biocompatibility, and non-toxicity to the human body. However, the current alloys available still have several issues, such as cytotoxicity of Al and V and high elastic modulus values, compared to human bone. β-type alloys, compared to α-type and (α + β)-type Ti alloys, have lower elastic modulus and higher mechanical strength. Then, new biomedical β-type alloys are being developed with non-cytotoxic alloying elements, such as Mo and Nb. Therefore, Ti-5Mo-xNb system alloys were prepared by argon arc melting. Chemical composition was evaluated by EDS analysis, and the density measurements were performed by Archimedes' method. The structure and microstructure of the alloys were obtained by X-ray diffraction and optical and scanning electron microscopy. Microhardness values were analyzed, and MTT and crystal violet tests were performed to assess their cytotoxicity. As the Nb concentration increases, the presence of the β-Ti phase also grows, with the Ti-5Mo-30Nb alloy presenting a single β-Ti phase. In contrast, the microhardness of the alloys decreases with the addition of Nb, except the Ti-5Mo-10Nb alloy, which has its microhardness increased probably due to the ω phase precipitation. Biological in-vitro tests showed that the alloys are not cytotoxic.